The Impact of Virtual Learning Environments on Student Achievement - Raziya Ademola (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The purpose of this research was to investigate whether or not there is a correlation between scholastic achievement, level of involvement, and level of satisfaction with Virtual Learning Environments (VLEs) among undergraduate students. The participants (N = 200) filled out self-report questionnaires regarding their scholastic achievement, involvement, level of contentment with virtual learning environments (VLEs), and punctuality. According to the findings, a student's level of contentment with their virtual learning environments was substantially associated with both their scholastic achievement (r =.53, p .001) and their level of involvement (r =.47, p .001). On the other hand, there was only a moderately strong association between punctuality and scholastic achievement (r =.25, p .01). These findings indicate that virtual learning environments (VLEs) can have a beneficial influence on the learning outcomes of students when they are successfully developed and implemented. The findings shed light on how critical it is to effectively create and implement VLEs in order to foster student involvement, inspiration, and scholastic achievement. These findings have significant repercussions for instructors and instructional programmers who work toward the goal of improving the learning outcomes of students by utilizing various forms of technology.